Fluvial processes: 2nd edition - Radecki-Pawlik, Artur (Geologos, 2019)
Book review: Fluvial processes: 2nd edition, by Ana Maria Ferreira da Silva and M. Selim Yalin, 2017. CRC Press, Boca Raton. 266 pages. Hardback: price £115,00, ISBN 9781138001381.